MOBILIZATION STRATEGIES AND YOUTH PARTICIPATION IN CONFLICT RESOLUTION COMMITTEE AS CORRELATES OF COMMUNITY DEVELOPMENT IN SOUTH EAST, NIGERIA - Igwe, Sunday; Umezulike, N. A.; Amadi , U. P. N. (Journal of Continuing and Development Education, 2024)
The study examined the mobilization strategies and youth participation in conflict resolution committee as correlates of community development in South East, Nigeria. Correlational design was used for this study. The targeted population for this study is 950 youth leaders from 95 local governments in South East Nigeria. The researcher targets 10 youth leaders from each local government area of each state that made-up South-East, Nigeria. The sample for the study was 950 community youth leaders in the 95 local government areas in the five (5) states of south east. There were no sampling technique since the population of the study is manageable and controllable by the researcher. Census sampling technique was used for this study. Mobilization Strategies for Youth Participation in Conflict Resolution Committee Questionnaire (MSYPCRCQ) and Community Development Questionnaire (CDQ)” were used for data collection. Two experts from the Department of Adult Education and one expert from the Department of Science Education validated the instruments. Cronbach alpha method was used to determine the reliability of the instrument which yielded an index of 0.70 for MSYPCRCQ and .81 for CDQ. Data collected from the field were analysed using Pearson Product Moment Correlation Coefficient to answer the research questions while t-test was used to test the formulated null hypotheses at 0.05 level of significance. Based on the analysis, the findings of the study revealed that; Youths’ participation in conflict resolution committee as a mobilization strategy significantly to a high positive extent relate to community development in the South-East Nigeria; and Mobilization strategies to a very high, positive extent predict youths’ participation in community development in the South-East Nigeria. Based on the findings of the study, the researcher recommends that; Government should through the ministry of youths’ development and other relevant ministries ensure that youth leaders form part of any conflict resolution committees being set up for any communities and Towns in conflicts; and that communities should ensure that their elders play only the advisory roles allowing the youths to get fully involved in the community development programmes